2011
DOI: 10.1136/heartjnl-2011-300065
|View full text |Cite
|
Sign up to set email alerts
|

Diffusion-weighted MRI determined cerebral embolic infarction following transcatheter aortic valve implantation: assessment of predictive risk factors and the relationship to subsequent health status

Abstract: Background 'Silent' cerebral infarction and stroke are complications of transcatheter aortic valve implantation (TAVI). Objective To assess the occurrence of cerebral infarction, identify predictive risk factors and examine the impact on patient health-related quality of life (HRQoL). Methods Cerebral diffusion weighted MRI of 31 patients with aortic stenosis undergoing CoreValve TAVI was carried out. HRQoL was assessed at baseline and at 30 days by SF-12v2 and EQ5D questionnaires. Results New cerebral infarct… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
100
2
1

Year Published

2013
2013
2018
2018

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 160 publications
(108 citation statements)
references
References 33 publications
3
100
2
1
Order By: Relevance
“…A comparable observation was reported by two other reports [5,7,18], with the largest portion of DWI lesions located on the left side of the brain. Two different hypotheses might explain this finding: (1) three major arteries, originating from the aortic arch, are at risk of receiving embolic particles from the calcified aortic valve and ascending aorta: the brachiocephalic, the left common carotid and the left subclavian arteries.…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…A comparable observation was reported by two other reports [5,7,18], with the largest portion of DWI lesions located on the left side of the brain. Two different hypotheses might explain this finding: (1) three major arteries, originating from the aortic arch, are at risk of receiving embolic particles from the calcified aortic valve and ascending aorta: the brachiocephalic, the left common carotid and the left subclavian arteries.…”
Section: Discussionsupporting
confidence: 92%
“…Future refinements to cerebral protection devices may offer full coverage of all three branch arteries of the aortic arch and hence better cerebral protection. With regard to potential risk factors for the development of new cerebral infarcts during TAVR, Fairbairn et al [7] reported old age and atherosclerotic burden of the aorta as independent predictors of the number of new cerebral ischemic lesions after these procedures. Astarci et al also found an association between age and the number of post-TAVR cerebral DWI lesions.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…KliniËki MU je bio povezan s veÊim brojem i volumenom infarkta. 58 Studija SIMPLIFy TAVI istraaeivala je da li izbjegavanje balonske valvuloplastike za predilataciju nativne aortne valvule smanjuje rizik od MU tijekom TAVI. OËekuje se da se u prospektivnom registru CoreValve Advance II definiraju naËini za smanjenje potrebe za ugradnjom trajnog elektrostimulatora srca.…”
Section: Aortic Valve Interventionsunclassified
“…Clinical stroke was associated with higher infarct number and volume. 58 The SIMPLIFy TAVI study (Transcatheter Aortic Valve Implantation Without Predilation) is investigating whether the avoidance of balloon valvuloplasty for predilation of the native aortic valve reduces the stroke risk during TAVI. The CoreValve Advance II prospective registry is expected to define ways to reduce the need for permanent pacemaker implantation.…”
Section: Ureaji Za Prevenciju Embolijementioning
confidence: 99%